Development of monoorganic and polyorganic phenotypes of bronchial asthma in children: the role of combined single-nucleotide variants - V.O. Dytiatkovskyi; O.L. Krivusha; N.M. Tokareva (Zaslavsky O.Yu., 2023)
Background. Bronchial asthma (BA) in children is on one of the leading places in the morbidity and mortality structure among other allergic and atopic diseases. It can be developed in the form of a monoorganic phenotype (MOPh) or a polyorganic phenotype (POPh) with other nosologies of atopic march (AM): atopic dermatitis (AD) and allergic rhinitis/rhinoconjunctivitis (AR/ARC). This process is genetically determined, with single-nucleotide variants (SNV) of filaggrin (FLG), thymic stromal lymphopoietin (TSLP) and orsomucoid-like protein 3 (ORMDL3) genes playing a major role. The purpose of this study was to reveal the impact of rs_7927894 FLG, rs_11466749 TSLP and rs_7216389 ORMDL3 SNV genotype combinations in the development of MOPh and POPh of atopic BA in children. Materials and methods. One hundred and twenty-one children of the main group and 105 controls took part in the study. The criteria for inclusion into the main group were: age from 3 to 18 years, clinically established and laboratory confirmed diagnoses of MOPh BA, POPh BA + AR/ARC and AD + AR/ARC + BA. The criteria for inclusion in the control group were: age from 3 to 18 years, excluded diagnoses of BA, BA + AR/ARC and AD + AR/ARC + BA. All children underwent swabbing of the oral mucosa and real-time polymerase chain reaction with the obtained material to detect variants of rs_7927894 FLG, rs_11466749 TSLP and rs_7216389 ORMDL3 genotype combinations. The results were processed using the following statistical tools: logistic regression analysis with determination of odds ratio (OR) with 95% confidence interval (95% CI), receiver operating characteristic (ROC) analysis with determination of the area under the ROC curve (AUC), sensitivity (Se), specificity (Sp), Pearson's correlation coefficient (r), Fisher's exact test, Student's t-test. The significance value was set at p < 0.05, trend to reliability - at p = 0.0-0.1. Results. The structure of the significantly most frequent genotypes in the cohorts of the main group was as follows: C/T rs_7927894 FLG + C/T rs_7216389 ORMDL3 - BA = 8.7 %; C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3: BA = 21.7 %, BA + AR/ARC = 18.1 %, AD + AR/ARC + BA = 15.4 %; C/T rs_7927894 FLG + A/A rs_11466749 TSLP: BA + AR/ARC = 31.9 %, AD + AR/ARC + BA = 42.3 %. Next, indicators of the genotypic combinations impact on the risk of BA phenotypes development related to the control group are provided. MOPh BA: C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3: r = 0.299, OR = 9.44 (95% CI 2.07-43.03), AUC = 0.594 (0.507-0.682), Se/Sp = 21.7/97.1 % (p < 0.001). POPh BA + AR/ARC: C/T rs_7927894 FLG + A/A rs_11466749 TSLP: r = 0.136, OR = 1.88 (95% CI 0.94-3.74), AUC = 0.560 (0.493-0.626), Se/Sp 31.9/80.0 % (p = 0.071); C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3: r = 0.260, OR = 7.49 (95% CI 2.05-27.37), AUC = 0.576 (0.528-0.624), Se/Sp = 18.1/97.1 % (p < 0.001). POPh AD + AR/ARC + BA: C/T rs_7927894 FLG + A/A rs_11466749 TSLP: r = 0.207, OR = 2.93 (95% CI 1.18-7.31), AUC 0.612 (0.507-0.716), Se/Sp =  42.3/80.0 % (р < 0.05); C/T rs_7927894 FLG + C/T rs_7216389 ORMDL3: r = 0.173, OR = 2.50 (95% CI 0.99-6.30), AUC = 0.592 (0.489-0.695), Se/Sp = 38.5/80.0 % (p < 0.05); C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3: r = 0.222, OR = 6.18 (95% CI 1.29-29.6), AUC = 0.563 (0.490-0.635), Se/Sp = 15.4/97.1 % (p < 0.01). The ratio of associations and risks for developing the phenotypes related to each other: BA + AR/ARC related to BA: C/T rs_7927894 FLG + C/T rs_7216389 ORMDL3: r = 0.171, OR = 3.50 (95% CI 0.75-16.41), AUC = 0.582 (0.504-0.659), Se/Sp = 25.0/91.3 % (p = 0.095); AD + AR/ARC + BA related to BA: C/T rs_7927894 FLG + C/T rs_7216389 ORMDL3: r = 0.345, OR = 6.56 (95% CI 1.26-34.23), AUC = 0.649 (0.537-0.761), Se/Sp = 38.5/91.3 % (р < 0.05); C/T rs_7927894 FLG + A/A rs_11466749 TSLP: r = 0.270, OR = 3.48 (95% CI 0.92-13.17), AUC = 0.625 (0.500-0.750), Se/Sp 42.3/82.6 % (p = 0.059). Conclusions. MOPh BA has a significant association and an increased risk of development with the SNV genotype combination C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3. POPh BA + AR/ARC has significant associations and increased risks of development with the following SNV genotype combinations: C/T rs_7927894 FLG + A/A rs_11466749 TSLP and C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3. POPh AD + AR/ARC + BA has the most associations and increased risks of development within the following SNV genotype combinations: C/T rs_7927894 FLG + A/A rs_11466749 TSLP, C/T rs_7927894 FLG + C/T rs_7216389 ORMDL3, C/T rs_7927894 FLG + T/T rs_7216389 ORMDL3.